2015
DOI: 10.1590/1414-431x20144213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salt intake and potassium supplementation on brachial-ankle pulse wave velocity in Chinese subjects: an interventional study

Abstract: Accumulating evidence has suggested that high salt and potassium might be associated with vascular function. The aim of this study was to investigate the effect of salt intake and potassium supplementation on brachial-ankle pulse wave velocity (PWV) in Chinese subjects. Forty-nine subjects (28-65 years of age) were selected from a rural community of northern China. All subjects were sequentially maintained on a low-salt diet for 7 days (3.0 g/day NaCl), a high-salt diet for an additional 7 days (18.0 g/day NaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…BaPWV and ABI were measured using a volume-plethysmographic apparatus (BP-203RPEII; Nihon Colin, Tokyo, Japan) [16, 17]. Participants were in the supine position with cuffs, which were connected to a plethysmographic sensor and an oscillometric pressure sensor, wrapped around both the brachium and ankles.…”
Section: Methodsmentioning
confidence: 99%
“…BaPWV and ABI were measured using a volume-plethysmographic apparatus (BP-203RPEII; Nihon Colin, Tokyo, Japan) [16, 17]. Participants were in the supine position with cuffs, which were connected to a plethysmographic sensor and an oscillometric pressure sensor, wrapped around both the brachium and ankles.…”
Section: Methodsmentioning
confidence: 99%
“…Thirty-one (31) studies examining arteriosclerosis were identified-of which, 14 were observational [15][16][17][18][19][20][27][28][29][30][31][32][33][34] and 17 were interventional [22,23,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Studies Investigating Arteriosclerosis (Arterial Stiffness)mentioning
confidence: 99%
“…From the 17 interventional studies investigating the association between arteriosclerosis [22,23,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], seven of them showed statistically significant changes in arterial stiffness biomarkers after Na intake intervention [35,37,38,[44][45][46]49]. On the contrary, 10 out of the 17 interventional studies found no changes in arterial stiffness biomarkers with various levels of Na intake during the intervention [22,23,36,[39][40][41][42][43]47,48] ( Table 2).…”
Section: Interventional Studiesmentioning
confidence: 99%
“…BP was measured by three trained staff members using a standard mercury sphygmomanometer, as previously described [23,24]. In brief, the subjects were instructed to rest in a sitting position for more than 5 min, and their right brachial pressure was measured while they were in a sitting position.…”
Section: Bp Measurementmentioning
confidence: 99%
“…baPWV Measurement baPWV was measured by standard method using tonometry as previously described [23]. Briefly, cuffs with a plethysmographic sensor that acquired waveform data and BP measurements were placed around the arms and ankles bilaterally (BP-203RPEII; Nihon Colin, Tokyo, Japan).…”
Section: Bp Measurementmentioning
confidence: 99%